Sustainable Development in ASEAN-5: Renewable Energy, Natural Resources Rent and Economic Globalization - Geubrina, Yulia; Aliasuddin, Aliasuddin; Abrar, Muhammad; Masbar, Raja; Saputra, Jumadil (International Journal of Business, Economics & Financial Studies, 2024)
Sustainable development has emerged as a critical global concern, particularly in the context of energy consumption and environmental quality. In Southeast Asia, the heavy reliance on fossil fuels, especially oil, poses significant challenges to achieving sustainability goals. This study investigates the impact of renewable energy consumption, natural resource rents, and economic globalization on the Sustainable Development Index (SDI). Using panel data from five ASEAN countries—Indonesia, Malaysia, Thailand, Singapore, and the Philippines—from 2000 to 2020, the analysis applies panel quantile regression to explore the relationships among the variables. The findings reveal that renewable energy consumption and economic globalization contribute positively to the Sustainable Development Index, whereas natural resource rents exhibit a negative impact. A distinctive aspect of this research is its use of the Sustainable Development Index as a metric, offering a novel approach not extensively employed in prior studies. The insights derived from this study can inform the development of policies promoting sustainable development, particularly through adopting renewable energy and managing economic globalization. Additionally, the findings underscore the need to address the adverse effects of natural resource exploitation to enhance regional sustainability outcomes.